STUDI KOMPARASI MENYIMPAN DAN MENAMPILKAN DATA HISTORI ANTARA DATABASE TERSTRUKTUR MARIADB DAN DATABASE TIDAK TERSTRUKTUR INFLUXDB - -, Hendra; Andriyani, Widyastuti (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
The use of structured databases is still very widely used by companies in small and medium scale with the aim of processing data so that from these data conclusions can be drawn to determine a decision. But over time, of course the need for data that continues to grow can make a system run very slowly when using a structured database. That is caused by the amount of data that continues to increase every day, even for certain cases the data can increase every second. For this reason, an unstructured database is needed specifically for storing history data. From some existing unstructured databases, InfluxDB is one of the unstructured databases specifically intended for storing history data and has a very good ability to process data into a matrix for analysis. One of the key factors in an unstructured database is the database structure which is very different and supports to maximize database performance.